Synthesized HMGB1 peptide attenuates liver inflammation and suppresses fibrosis in mice - Shunsuke Nojiri; Atsunori Tsuchiya; Kazuki Natsui; Suguru Takeuchi; Takayuki Watanabe; Yuichi Kojima; Yusuke Watanabe; Hiroteru Kamimura; Masahiro Ogawa; Satoko Motegi; Takahiro Iwasawa; Takeki Sato; et al. (BMC, 2021)
Abstract The liver has a high regenerative ability and can induce spontaneous regression of fibrosis when early liver damage occurs; however, these abilities are lost when chronic liver damage results in decompensated cirrhosis. Cell therapies, such as mesenchymal stem cell (MSC) and macrophage therapies, have attracted attention as potential strategies for mitigating liver fibrosis. Here, we evaluated the therapeutic effects of HMGB1 peptide synthesized from box A of high mobility group box 1 protein. Liver damage and fibrosis were evaluated using a carbon tetrachloride (CCl4)-induced cirrhosis mouse model. The effects of HMGB1 peptide against immune cells were evaluated by single-cell RNA-seq using liver tissues, and those against monocytes/macrophages were further evaluated by in vitro analyses. Administration of HMGB1 peptide did not elicit a rapid response within 36 h, but attenuated liver damage after 1 week and suppressed fibrosis after 2 weeks. Fibrosis regression developed over time, despite continuous liver damage, suggesting that administration of this peptide could induce fibrolysis. In vitro analyses could not confirm a direct effect of HMGB1 peptide against monocyte/macrophages. However, macrophages were the most affected immune cells in the liver, and the number of scar-associated macrophages (Trem2+Cd9+ cells) with anti-inflammatory markers increased in the liver following HMGB1 treatment, suggesting that indirect effects of monocytes/macrophages were important for therapeutic efficacy. Overall, we established a new concept for cell-free therapy using HMGB1 peptide for cirrhosis through the induction of anti-inflammatory macrophages.